2006
DOI: 10.1159/000096316
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Episodic Memory in Persons with Mild Cognitive Impairment and Healthy Older Adults: Evidence from a Cognitive Intervention Program

Abstract: The efficacy of cognitive training was assessed in persons with mild cognitive impairment (MCI) and persons with normal cognitive aging. Forty-seven participants were included in this study: 28 with MCI and 17 controls. Twenty-one participants received intervention (20 MCI and 9 controls) and 16 participants (8 MCI and 8 controls) received no intervention (waiting-list group). The intervention focused on teaching episodic memory strategies. Three tasks of episodic memory (list recall, face-name association, te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
281
2
40

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(347 citation statements)
references
References 90 publications
24
281
2
40
Order By: Relevance
“…To date, most interventions aimed at improving face-name memory in older adults have focused on training explicit memory strategies (Hampstead et al, 2008) and imagery (Belleville et al, 2006). Extrapolating from the current results, future interventions may capitalize on older adults' natural tendency to tacitly rely on incidentally encoded information at retrieval (Biss, Ngo, et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…To date, most interventions aimed at improving face-name memory in older adults have focused on training explicit memory strategies (Hampstead et al, 2008) and imagery (Belleville et al, 2006). Extrapolating from the current results, future interventions may capitalize on older adults' natural tendency to tacitly rely on incidentally encoded information at retrieval (Biss, Ngo, et al, 2013).…”
Section: Discussionmentioning
confidence: 91%
“…A clinical trial of memory training in 19 MCI patients did not show a positive effect of training at immediate post-test or six month follow-up (only 1 of 16 comparisons were significant; (Rapp et al, 2002). In another study that included mnemonic training techniques similar to those used in ACTIVE (e.g., imagery, organization, method of loci) that were imbedded within dual-task attention training, MCI adults benefited from training on some immediate post-test measures of face-name associations but not on measures of paragraph recall or immediate word list recall (Belleville et al, 2006). Although the Belleville et al study had a small sample size (20 MCI subjects and 9 controls), their results suggest that to improve memory function in MCI patients, a more multi-factorial approach than the ACTIVE training may be required.…”
Section: Discussionmentioning
confidence: 99%
“…Belleville performed episodic memory training for MCI patients, including list recall, face-name memory strategies, and text memory. The results showed that memory capacity of patients with MCI were significantly improved [5].…”
Section: Introductionmentioning
confidence: 94%